Research methodology knowledge between master and doctoral education research students - Yusof, I. J. (Assoc Acad Propriedade Intelectual, 2021)
Knowledge of research methodology is important for those who are required to read research articles. With the knowledge of research methodology, students will be able to evaluate whether the methods employed by the author is appropriate for the study. However, the differences in research experience between master and doctoral students influence their expectation of research methodology course. This paper examined the level of research methodology knowledge of master and doctoral research students in education after attending a series of research methodology courses. Based on 39 respondents, this paper revealed that both groups are at Moderate Low level. Further analysis revealed that 44.4% of master students are at Low level compared to only 23.8% of doctoral students who are found at the Low level. It was also revealed that both groups have difficulties in quantitative research concepts specifically on research design, sampling, and data collection topics. The most common suggestions received from master students are to segregate the course between master and doctoral students and to have more specific content on the course. Future study should have more representatives of postgraduate students and larger samples for inferential statistics to compare mean between the groups and to examine the association between research experiences and research methodology knowledge.